Characteristics of Albumin Levels and Liver Function in Patients With COVID-19 at H. Adam Malik Hospital, Medan - Ghazali Akhmad Putranta; Fajrinur Syarani; Syamsul Bihar; Putri Chairani Eyanoer (Indonesian Society of Respirology (ISR), 2022)
Background: COVID-19 (Corona Virus Disease-2019) pandemic has a high mortality rate especially in Medan, Indonesia. Serum albumin and liver function tests are believed to be predictive biomarkers for prognosis in patients with infectious diseases, including COVID-19. This study aimed to investigate the association between the mortality events and severely ill COVID-19 patients' serum albumin and liver enzymes. Method: This is a cross-sectional study using secondary data from the medical records of H. Adam Malik Hospital patients with COVID-19 who were confirmed by RT-PCR from August to December 2020. All patients were analyzed for age, sex, hypoalbuminemia, increased liver enzymes and outcome using Chi-square tests (P<0.05). Results: The average age of severe COVID-19 patients at H. Adam Malik Hospital ranged from 41 to 60 years, with more women prevalence than men. Most of the patients had hypoalbuminemia (84.2%), an increase in AST (59.4)% and ALT (45.5%). There was no significant association between hypoalbuminemia and the disease outcome (P=0.12). There was a significant association between elevated liver enzymes and mortality in severely ill COVID-19 patients (P<0.001). Conclusion: We found that hypoalbuminemia is common in patients with severe COVID-19. However, we found that albumin levels had no association with the patients' mortality rate. Liver enzymes levels appear to be a predictive biomarker for outcomes in COVID-19 patients of H. Adam Malik Hospital. We found that higher ALT and AST levels were associated with significantly higher mortality.